Effectiveness of rehabilitation intervention in persons with Friedreich ataxia - Paparella, Gabriella; Stragà, Cristina; Vavla, Marinela; Pesenti, Nicola; Merotto, Vasco; Martorel, Gian A.; Zalunardo, Sara; Armellin, Maria; Comiotto, Jimmy; Martinuzzi, Andrea (Frontiers in Neurology, 2023)
Introduction The relevance of rehabilitation in progressive neurological disorders, such as Friedreich’s Ataxia (FRDA), has yet to be convincingly proven. FRDA is characterized by ataxia, loss of gait, scoliosis, cardiomyopathy, dysarthria and dysphagia, with reduced life expectancy. The disease onset is usually in adolescence, leading to progressive disability. Omaveloxolone has been recently approved as the first pharmacological treatment for FRDA in adults and adolescents aged 16 years and older. Regarding non-pharmacological therapies, neurorehabilitation is a valuable aid in addressing the symptoms and in maintaining the residual functioning. We performed a prospective observational cohort study to evaluate the efficacy of inpatient rehabilitation (IR) for people with FRDA. Methods A total of 42 individuals (29 adults and 13 children) with FRDA were recruited. There were 27 ambulant and 15 non-ambulant participants. The patients underwent IR of 3 and 4 weeks in children and adults, respectively. The IR treatment was designed to be applied within a multidisciplinary setting, so FRDA patients underwent, in addition to physiotherapy, also occupational therapy, practical manual activities and psychological support aiming to enhance transferable skills useful in the activities of daily living. The primary outcome was the Scale for the Assessment and Rating of Ataxia (SARA). Other measures were: Friedreich Ataxia Rating Scale (FARS) and Nine Hole Peg Test (NHPT). Furthermore, we used the 6 Minute Walk Test (6MWT), the Timed Up and Go (TUG) and the Berg Balance Scale (BBS) only on ambulant subjects. Outcomes were evaluated at baseline and at the end of the treatment. Results We report that the IR significantly improves motor performance and ataxia symptoms in patients with FRDA. Our study shows significant functional improvement in all the outcome measures used, except for NHPT bilaterally. FARS and SARA scores post-IR are significatively reduced when compared (p < 0.001). Discussion We demonstrate that IR programs in FRDA can provide a meaningful clinical improvement in terms of outcome measures. These findings could be useful when approaching progressive neurological disorders.